Digit span and other WISC-R scores in the diagnosis of dyslexia in children - Vargo, F E; Grosser, G S; Spafford, C S (Perceptual and motor skills, 1995)
The examination of subtest scores on the Wechsler Intelligence Scale is needed to provide confirmatory evidence for various subtest categorizations as there is no consensus about what patterns might be diagnostically useful. The present study supports the use of the ACID/AVID profiles (Arithmetic, Coding or Vocabulary, Information, and Digit Span) as elements in the diagnosis of dyslexia. WISC-R scores from 44 subjects were analyzed for specific subtest patterns of scores which might separate dyslexic individuals from the WISC-R standardization group. Perhaps some WISC-R ACID/AVID profile pattern analyses may be valid in the diagnosis of a stringently defined population of learning disabled individuals such as dyslexic children.